Pengaruh Pendidikan Akhlak terhadap Perilaku Santri di Pondok Pesantren As-Shiddiqiyah - Ummu Kulsum (Qiro'ah : Jurnal Pendidikan Agama Islam, 2021)
This study entitled about education involves many things that must be pondered. Because education includes all human behavior that is carried out for the sake of obtaining continuity, defense and improvement of life. In the language of religion, in order to gain the pleasure of Allah. So that the whole behavior forms the integrity of a virtuous human being (having good character). The urgency of moral education for students or society because it is something that becomes behavior (Sulukiyah) in everyday life and becomes a mirror of one's life in society and the state. To achieve these objectives the researchers used a quantitative approach. Data collection techniques using interviews, observation, interviews and questionnaires. The data analysis technique uses data interpretation analysis using the Simple Regression formula. The results of this study indicate that there are three models of moral education. The First is a rational moral model. The Second is a religious moral model. The Third is an eclectic moral model. Asshiddiqiyah Islamic boarding school in its moral education uses an eclectic moral education model. The results of this study indicate that moral education carried out in Islamic boarding schools can have a very significant influence on the behavior of students, this can be seen from the results of the questionnaire calculation, namely the t count is greater than 19,041 than t. the table is good at a significant level of 0.05: 3.99 and at a level of 0.01: 7.04, so the magnitude of rxy is 0.219, which is = 0.219. which implies that 21.9% of the variation in student behavior can be explained by moral education.